Determining 1st– 4th Grade Elementary School Students’ Perceptions of Scientists - KABATAŞ MEMİŞ, Esra; ÇAKAN AKKAŞ, Büşra Nur; KETENOĞLU KAYABAŞI, Zehra Esra; KARAKUŞ, Esma; FİLİZ, Nurullah (Babes-Bolyai University, 2020)
Abstract: The main purpose of this study is to determine the perceptions of elementary school students (1,2,3 and 4) about science and scientist. The study has been included three different elementary schools in the city center of Kastamonu in northwest Turkey. A total of 1862 students in the first (n = 480), second (n = 450), third (n = 471) and fourth (n = 461) classes participated in the study. The Draw-a-Scientist Test (DAST) developed by Chambers (1983) was used to determine the views of students about scientists. The content of the collected data was analyzed. It was found that the majority of the students, in total and at all grades, drew pictures of male scientists. It was determined that they made drawings of scientists who were in daily clothes, had well-groomed hair and were working in different environments (nature, space, etc.).
Keywords: 4. Education; 11. Sustainability